A Studi Dinamika Kelompok Nelayan Jaringan Insang (Gillnet) Karyamaju Bersama Di Desa Sungai Meriam Kecamatan Anggana Kabupaten Kutai Kartanegara: Dinamika Kelompok - Dewi Wijayanti; Helminuddin; Elly Purnamasari (2339-1324, 2023)
The purpose of this study is to explain group dynamics and identify problemsfaced by Karyamaju Bersama gillnet fishermen. This entire series of research wascarried out for 13 months starting from January 2021 to January 2022 with theresearch location in Sungai Meriam Village, Anggana District, Kutai KartanegaraRegency.Sampling referstothecensus method,whereall14 membersofthepopulation are all respondents. Field data collection by means of observation andinterviews using a questionnaire. To measure the level of group dynamics of gill netfishermen, the data was processed using the Likert scale method, namely giving ascore for each respondent's answer, namely the highest answer was given a score of3 and the lowest was given a score of 1. The results showed that the level of groupdynamics of gill net fishermen ( Gill net) Karyamaju Bersama got a score of 79.0 intherange (64.00–81.00) whichmeans High(Dynamic).Keywords:GroupDynamics,“KaryamajuBersama”GillnetFishermenGroup,SungaiMeriam. Villag